KONTRIBUSI JASSER AUDA DALAM KAJIAN AL-QUR’AN: INTERPRETASI BERBASIS SISTEM - Dayu Aqraminas (Ushuluna: Jurnal Ilmu Ushuluddin, 2018)
This article explores the contribution of Jasser Auda in developing the theory of Maqāṣid Al-Sharī'ah, especially in the field of Tafsir al-Qur’an. Through a qualitative approach, the data related to the study of the Qur'an, Jasser Auda and Maqāṣid Al-Sharī'ah, are explained descriptively-analytically. From this description, we get the real role of Auda, namely the application of system-based interpretation in the implementation of tafsīr maqāṣidī. This article also explains features that affect the system approach, as well as the operational stages of the theory.